Validity of diagnostic codes and laboratory tests of liver dysfunction to identify acute liver failure events. (10th April 2015) - Lo Re, Vincent; Carbonari, Dena M.; Forde, Kimberly A.; Goldberg, David; Lewis, James D.; Haynes, Kevin; Leidl, Kimberly B. F.; Reddy, Rajender K.; Roy, Jason; Sha, Daohang; Marks, Amy R.; Schneider, Jennifer L.; et al.
Abstract Purpose Identification of acute liver failure (ALF) is important for post‐marketing surveillance of medications, but the validity of using ICD‐9 diagnoses and laboratory data to identify these events within electronic health records is unknown. We examined positive predictive values (PPVs) of hospital ICD‐9 diagnoses and laboratory tests of liver dysfunction for identifying ALF within a large, community‐based integrated care organization. Methods We identified Kaiser Permanente Northern California health plan members (2004–2010) with a hospital diagnosis suggesting ALF (ICD‐9 570, 572.2, 572.4, 572.8, 573.3, 573.8, or V42.7) plus an inpatient international normalized ratio ≥1.5 (off warfarin) and total bilirubin ≥5.0 mg/dL. Hospital records were reviewed by hepatologists to adjudicate ALF events. PPVs for confirmed outcomes were determined for individual ICD‐9 diagnoses, diagnoses plus prescriptions for hepatic encephalopathy treatment, and combinations of diagnoses in the setting of coagulopathy and hyperbilirubinemia. Results Among 669 members with no pre‐existing liver disease, chart review confirmed ALF in 62 (9%). Despite the presence of co‐existing coagulopathy and hyperbilirubinemia, individual ICD‐9 diagnoses had low PPVs (range, 5–15%); requiring prescriptions for encephalopathy treatment did not increase PPVs of these diagnoses (range, 2–23%). Hospital diagnoses of other liver disorders (ICD‐9 573.8) plus hepatic coma (ICD‐9 572.2) had high PPV (67%; 95%CI, 9–99%) but only identified two (3%) ALF events. Conclusions Algorithms comprising relevant hospital diagnoses, laboratory evidence of liver dysfunction, and prescriptions for hepatic encephalopathy treatment had low PPVs for confirmed ALF events. Studies of ALF will need to rely on medical records to confirm this outcome. Copyright © 2015 John Wiley & Sons, Ltd.